HER2 antibody-drug conjugate controls growth of breast cancer brain metastases in hematogenous xenograft models, with heterogeneous blood–tumor barrier penetration unlinked to a passive marker. Issue 11 (9th May 2020) - Gril, Brunilde; Wei, Debbie; Zimmer, Alexandra S; Robinson, Christina; Khan, Imran; Difilippantonio, Simone; Overstreet, Michael G; Steeg, Patricia S
Abstract: Background: Brain metastases of HER2+ breast cancer persist as a clinical challenge. Many therapeutics directed at human epidermal growth factor receptor 2 (HER2) are antibodies or antibody-drug conjugates (ADCs), and their permeability through the blood–tumor barrier (BTB) is poorly understood. We investigated the efficacy of a biparatopic anti-HER2 antibody-tubulysin conjugate (bHER2-ATC) in preclinical models of brain metastases. Methods: The compound was evaluated in 2 hematogenous HER2+ brain metastasis mouse models, SUM190-BR and JIMT-1-BR. Endpoints included metastasis count, compound brain penetration, cancer cell proliferation, and apoptosis. Results: Biparatopic HER2-ATC 3 mg/kg prevented metastasis outgrowth in the JIMT-1-BR model. At 1 mg/kg bHER2-ATC, a 70% and 92% reduction in large and micrometastases was observed. For the SUM190-BR model, an 85% and 53% reduction, respectively, in large and micrometastases was observed at 3 mg/kg, without statistical significance. Proliferation was reduced in both models at the highest dose. At the endpoint, bHER2-ATC uptake covered a median of 4–6% and 7–17% of metastasis area in the JIMT-1-BR and SUM190-BR models, respectively. Maximal compound uptake in the models was 19% and 86% in JIMT-1-BR and SUM190-BR, respectively. Multiple lesions in both models demonstrated ADC uptake in the absence or low diffusion of Texas Red Dextran, a marker of paracellular permeability. Using in vitro BTB assays, the ADC was endocytosed into brain endothelial cells, identifying a potentially new mechanism of antibody permeability. Conclusions: Biparatopic HER2-ATC significantly prevented JIMT-1-BR brain metastasis outgrowth and showed activity in the SUM190-BR model. The bHER2-ATC penetration into metastases that are impermeable to fluorescent dye suggested an endocytic mechanism of brain penetration.